A study of young women consumers' attitudes and purchase intentions towards luxury apparel & accessories in India - Singh, Neetu (2023)
This research provides empirical support to the luxury value perception model (LVP) created by Wiedmann et al. (2009) influencing purchase intentions of luxury apparel and accessories of young generation Z women consumers, categorizing their value perceptions across functional, individual, and social dimensions. Data collected through a questionnaire across 209 generation Z women consumers of India and analyzed using structural equation modeling, depicts a positive relationship between Self-identity and Prestige in social networks with purchase intention of luxury fashion and accessory brands of young women consumers. Hence, the high involvement of consumers with luxury fashion brands directly influences their self-concept and low prestige in social networks inversely leads the consumers to make high-value luxury purchases. The findings of this research provide valuable insights to build business practices and strategies of luxury fashion and accessory brands trying to gain inroads in the Asian and most preferably Indian markets